PEMBERDAYAAN MASYARAKAT DALAM PEMANFAATAN CHLORELLA SEBAGAI PAKAN IKAN GURAMI DAN PENDAMPINGAN EVALUASI MANAJEMEN USAHA BUDIDAYA IKAN - Welmar Olfan Basten Barat; Tambos Sianturi; Mardame Sinaga (Yayasan Nusantara Hasana Berdikari, 2025)
Tanjung Seri Village is a village in Laut Tador District, Batu Bara Regency, North Sumatra Province, Indonesia. The residents of Tanjung Seri Village are fish farmers, farmers, and traders. The national potential for aquaculture is estimated at 17.92 million hectares, including 2.83 million hectares of freshwater aquaculture. Feed that meets fish nutritional needs can improve the growth of fish fry to marketable size. The Tanser SPN Bersama community group and the Community Partnership Empowerment (PKM) team discussed the problems experienced by their partners, thus forming conclusions about the problems to be resolved, namely in the areas of production and management. Community partnership empowerment activities for productive economic partners, namely the gourami farmer group, namely: TANSER SPN BERSAMA are carried out in 5 stages in implementing the solutions offered, namely socialization, training, mentoring, monitoring and evaluation and application of technology. The results of the evaluation of the gourami fish business evaluation training program show that 10% have understood the outline of the evaluation of catfish farming management business, after the training, 100% of community groups know catfish farming management, there is an increase of 90% from the 10 respondents recorded.